بزوتنەوەی ڕووناكبیری لە ئەدەبی كوردیدا بە نموونەی "ئەسیری" شاعیر - مەحمود, فازیل مەجید; مەجید, سەردار فایەق (Sulaimani Journal for Humanities, 2018)
The intellectual movement was a global and comprehensive movement, that’s why the poets in this movement represented their society through their specialties and skills. They tried to aware people through their poetical achievements, they also tried to make the society have a modern intellectual view in the fields of social, cultural, educational, political and religious to show vicious phenomenons in the society and humanitarian values, what needs to be mentioned here is that the Kurdish intellectual movement has it’s own cultural, social, ideological... etc, characteristics. This paper consists of an introduction and two chapters, the first chapter deals with Ahmedi Khani, Haji Qadri Koiy, Hamdi intellectual idiosyncrasy. The second chapter concentrates on intellectual specialties in Asiry’s poetries. The final part of the paper is the conclusion, in which we’ve concluded the outcome in some points.